2004
DOI: 10.1021/la035774i
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Behavior of Thermotropic Liquid Crystals on Surfaces Presenting Electrostatically Bound Vesicular Stomatitis Virus

Abstract: We report the orientational behavior of nematic phases of 4-cyano-4'-pentylbiphenyl (5CB) on cationic, anionic, and nonionic surfaces before and after contact of these surfaces with solutions containing the negatively charged vesicular stomatitis virus (VSV). The surfaces were prepared on evaporated films of gold by either adsorption of poly-L-lysine (cationic) or formation of self-assembled monolayers (SAMs) from HS(CH2)2SO3- (anionic) or HS(CH2)11(OCH2CH2)4OH (nonionic). Prior to treatment with virus, we mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…The LC‐filled grids were supported on a glass microscope slide treated with octadecyltrichlorosilane (OTS). The OTS treatment of the glass anchors 5CB and a variety of other LCs in an orientation that is perpendicular (homeotropic) to the LC‐glass interface 44, 45. The results reported below indicate that mixtures of 5CB and EG4‐LC also assume a homeotropic orientation at the surface of OTS‐treated glass.…”
Section: Resultsmentioning
confidence: 72%
“…The LC‐filled grids were supported on a glass microscope slide treated with octadecyltrichlorosilane (OTS). The OTS treatment of the glass anchors 5CB and a variety of other LCs in an orientation that is perpendicular (homeotropic) to the LC‐glass interface 44, 45. The results reported below indicate that mixtures of 5CB and EG4‐LC also assume a homeotropic orientation at the surface of OTS‐treated glass.…”
Section: Resultsmentioning
confidence: 72%
“…Because many viruses, bacteria as well as mammalian cells are encapsulated by lipid membranes, recent studies have been performed to investigate their interactions with LCs. These studies have demonstrated that contact between LCs and lipid-encapsulated viruses [86, 103, 104] and gram-negative bacteria [86, 105] can drive ordering transitions within the LC, implicating LCs as potentially useful sensors of these virions and microorganisms. This is a promising capability, as the rapid and sensitive detection of harmful microorganisms and infectious agents is important for upholding public health and safety in areas including food processing, water and environmental monitoring, and clinical diagnostics [106].…”
Section: Lcs As Sensors Of Viruses Bacteria and Mammalian Cellsmentioning
confidence: 99%
“…Espinoza et al [103] first demonstrated that LCs can be utilized for the detection of lipid-encapsulated viruses. Solutions of vesicular stomatitis virus (VSV) were incubated on the surface of gold slides treated with poly- l -lysine.…”
Section: Lcs As Sensors Of Viruses Bacteria and Mammalian Cellsmentioning
confidence: 99%
“…This aspect of LC-based systems has been exploited to develop new sensing platforms that can report on the presence and/or organization of chemical or biological agents 4-17. For example, several recent studies have demonstrated that ordering transitions in LCs can be triggered by the adsorption of phospholipids,4,18-20 surfactants,21-25 polymers,14,26,27 proteins,4,9-11,28,29 viruses,8,13,17 and bacteria17 at interfaces created between LCs and solid substrates5-10,12,13,29 or LCs and aqueous phases 4,11,14-28. The results of these past studies have suggested new principles and approaches for the design of LC-based systems that have relevance in a broad range of fundamental and applied contexts (e.g., sensing).…”
Section: Introductionmentioning
confidence: 99%